2017
DOI: 10.1107/s2053229617011160
|View full text |Cite
|
Sign up to set email alerts
|

Invariom-model refinement and Hirshfeld surface analysis of well-ordered solvent-free dibenzo-21-crown-7

Abstract: Crown ethers and their supramolecular derivatives are well-known chelators and scavengers for a variety of cations, most notably heavier alkali and alkaline-earth ions. Although they are widely used in synthetic chemistry, available crystal structures of uncoordinated and solvent-free crown ethers regularly suffer from disorder. In this study, we present the X-ray crystal structure analysis of well-ordered solvent-free crystals of dibenzo-21-crown-7 (systematic name: dibenzo[b,k]-1,4,7,10,13,16,19-heptaoxacycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Since a broad peak around q = 0.5 Å −1 has also been observed in the pXRD pattern of CsI-DB21C7 powder, this peak might therefore arise from the formation of crystals of CsI-DB21C7. To verify this hypothesis, we generated a crystal structure of CsI-DB21C7 based on previously reported crown ether crystal structures 26 (Supplementary Fig. 7d) and optimized it by using density functional theory (DFT) calculations (computational details provided in the Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Since a broad peak around q = 0.5 Å −1 has also been observed in the pXRD pattern of CsI-DB21C7 powder, this peak might therefore arise from the formation of crystals of CsI-DB21C7. To verify this hypothesis, we generated a crystal structure of CsI-DB21C7 based on previously reported crown ether crystal structures 26 (Supplementary Fig. 7d) and optimized it by using density functional theory (DFT) calculations (computational details provided in the Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Concentration-dependent 1 H NMR spectroscopy of CE 2 showed slight downfield shift of CH 2 protons, supporting that CH···O H bonding is operative in gels (Figure S2). Similarly, analyses of the reported crystal structures of other crown ethers ( 1 , 3 – 5 ) revealed that they also use weak CH···O H bonding and C–H···π interactions for their self-assembly, and comparison of PXRD patterns of their xerogels with the simulated powder patterns from their crystal structures revealed that they also have conserved molecular arrangement in crystals and gels (Figure S3).…”
Section: Introductionmentioning
confidence: 85%
“…Hirshfeld surface analysis and fingerprint plots, here generated with Crystal Explorer (Hirshfeld, 1977;Wolff et al, 2012;Turner et al, 2017), show the various intermolecular interactions present in crystal structures (Wiedemann & Kohl, 2017;Tarahhomi et al, 2013). Fig.…”
Section: Hirshfeld Surface Analysismentioning
confidence: 99%